2011
DOI: 10.1007/s10750-011-0690-8
|View full text |Cite
|
Sign up to set email alerts
|

Sampling macroinvertebrates in a temporary pond: comparing the suitability of two techniques to detect richness, spatial segregation and diel activity

Abstract: Recent and increasing interest in temporary ponds as biodiversity reservoirs fosters our need to test sampling techniques for characterising their biological communities. We compared the efficiency of dip-netting to that of fyke nets in sampling the macroinvertebrate assemblage of a temporary pond in Doñana National Park (SW Spain). We sampled the pond at four different times-morning, afternoon, evening and night-distinguishing between deep and shallow zones. In our sampling, dip-netting captured a higher numb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 39 publications
(62 reference statements)
0
17
0
Order By: Relevance
“…For instance in lentic ecosystems, Florencio et al (2011) suggested that dip-netting was especially appropriate for sampling macroinvertebrates in different microhabitats, whereas fyke nets were a better option for capturing nocturnal and fast-swimming invertebrates. Similar problems may affect lotic ecosystems, where the use of a Surber sampler alone might not be capable of collecting fast-swimming invertebrates like some Coleoptera (e.g., family Gyrinidae), or skaters like aquatic Hemiptera (e.g., Gerridae).…”
Section: Final Remarks and Future Research Linesmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance in lentic ecosystems, Florencio et al (2011) suggested that dip-netting was especially appropriate for sampling macroinvertebrates in different microhabitats, whereas fyke nets were a better option for capturing nocturnal and fast-swimming invertebrates. Similar problems may affect lotic ecosystems, where the use of a Surber sampler alone might not be capable of collecting fast-swimming invertebrates like some Coleoptera (e.g., family Gyrinidae), or skaters like aquatic Hemiptera (e.g., Gerridae).…”
Section: Final Remarks and Future Research Linesmentioning
confidence: 99%
“…feeding or avoiding predation, Elliott 2000Elliott , 2002Hampton and Duggan, 2003;Florencio et al, 2011). In a North American stream, for example, it has been observed that several caddisfly larvae (Sericostomatidae) burrow during the day and resurface at night (Bergey and Resh, 1994).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The absence of this group in fishless ponds (which were also the ones with high trophic level) could be caused by the shift from benthic to pelagic production as mentioned above, but also because of the lack of macrophytes. The sampling methodology used for large invertebrates (corer) could also have some limitations when sampling insects with high mobility in the water column, as these active taxa are more difficult to detect with usual sampling techniques for planktonic organisms (Florencio et al, 2012). Malacostraceans presented the highest richness in the recently created pond SA, which had total richness values similar to the other ponds.…”
Section: Influence Of Fishmentioning
confidence: 99%
“…Thus, their abundance is frequently difficult to estimate when the whole water column (including watersediment interface) is not completely sampled. In addition, the sampling methodology or the microhabitat sampled are often determinant to estimate the different community parameters (Garcı´a-Criado and Trigal, 2005;Florencio et al, 2012). Quantitative studies on aquatic invertebrates are mostly focused on microzooplankton (e.g., rotifers and juvenile copepods), macrozooplankton (e.g., adult copepods and cladocerans) or macroinvertebrates (e.g., bigger crustaceans and insects) separately, and usually interactions among them have not been largely considered.…”
Section: Introductionmentioning
confidence: 99%